Investigating the Interhemispheric Asymmetry in Joule Heating During the 2013 St. Patrick's Day Geomagnetic Storm - A. R. Smith; D. S. Ozturk; P. Delamere; G. Lu; H. Kim (Space Weather)
Abstract Sudden changes in energy input from the magnetosphere during geomagnetic storms could drive extreme variability in the ionosphere‐thermosphere system, which in turn affect satellite operations and other modern infrastructure. Joule heating is the main form of magnetospheric energy dissipation in the ionosphere‐thermosphere system, so it is important to know when and where Joule heating will occur. While Joule heating occurs all the time, it can increase rapidly during geomagnetic storms. We investigated the Joule heating profile of the 2013 St Patrick's day storm using the University of Michigan Global Ionosphere‐Thermosphere Model (GITM). Using empirical and data‐assimilated drivers we analyzed when and where intense Joule heating occurred. The timing, location, and sources of interhemispheric asymmetry during this geomagnetic storm are of key interest due to near equinox conditions. Hemispheric comparisons are made between parameters, including solar insolation, total electron content profiles, and Pedersen and Hall conductance profiles, obtained from GITM driven with empirical driven input, versus those driven with data‐assimilated patterns. Further comparisons are made during periods of peak hemispheric Joule heating asymmetry in an effort to investigate their potential sources. Additionally, we compare the consistency of the interhemispheric asymmetry between empirical‐ and data‐assimilated driven simulations to further analyze the role of data‐assimilated drivers on the IT system.